Percutaneous pulmonary valve implantation and related risk of coronary compression – a case report - Demkow, Marcin; Biernacka, Katarzyna; Kalińczuk, Łukasz; Śpiewak, Mateusz; Moll, Jadwiga; Hoffman, Piotr; Rużyłło, Witold (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2010)
A case of 17-year-old boy with heart catheterisation before planned transcatheter implantation of a pulmonary valve for severe stenosis of his previousely implanted pulmonary homograft is reported. Coronary angiography during simultaneous test inflation of a balloon in the place of homograft stenosis showed severe compression of right coronary artery. This disappeared after balloon deflation. The valve implantation was abandoned. The described test is recommended as a routine before transcatheter pulmonary valve implantation.